Regulation of protein and carbohydrate intake in caged honeybees Apis mellifera scutellata : assessment based on consumption and various performance measures - Pirk, Christian Walter Werner (University of Pretoria, 2013)
Dissertation (MScAgric)--University of Pretoria, 2010.